Mercaderes genoveses en Málaga (1487-1516): los hermanos Centurión e Ytalián. - López Beltrán, María Teresa; López de Coca Castañer, José Enrique (Historia. Instituciones. Documentos, 2018)
RESUMEN: ABSTRACT: